Standards for land use and planning - Only for specialists? - Paasch, Jesper M.; Paulsson, Jenny (TU Wien, 2016)
Standards have become vital instruments for describing and structuring e.g. real property rights and planning information, such as the international Land Administration Domain Model and the national Swedish standard for detailed development plans. However, the publication of a standard does not automatically ensure that it is used or understood. Standards are primarily technical documents and not easily accessible by non-specialists. This article discusses the problems of using standards; such as the use of terminology and to access specific target group(s) when implementing standards in the geoformation sector in general and standards on property rights and planning in the public sector in particular. Conclusions are that a standard in itself may be of rather little value if not assisted by additional, non-expert documents for a broader group(s) of decision makers and other non-experts within the organization, aiming at different organizational levels.
Keywords: Raumplanung; Terminologie; Theorie; Planungsprozess; Standardisierung; Flächennutzung; Flächenplanung; Standard; Informationsmanagement; Geoinformation